Formação em Comunicação Social/Jornalismo na Região Norte: um estudo sobre alterações nas universidades federais a partir de 2013 - Silva, Sinomar Soares de Carvalho (2019)
This dissertation focuses on Social Communication / Journalism training with special attention to the Northern Region of Brazil. The general objective is to analyze how the pedagogical projects of the federal universities are organized after the adoption of the new curricular guidelines in 2013. In order to reach this goal we have established three specific paths: to describe elements that have been renounced and adopted in PPCs based on the guidelines of the new guidelines, identify how the instrumentalization of the supervised internship was made and establish relationships among the new curricula to find the directions that they point out. In order to achieve these objectives, we use bibliographical and documentary research with qualitative and quantitative approaches. We also used content analysis techniques (BARDIN, 1977) to examine the data collected. The treatment of this data was done through Iramuteq software, which was developed with open license and is freely available for download on the internet. In addition to this software we use other programs to obtain information about the teaching production at the undergraduate and graduate levels between the years 2015 and 2017. When we are faced with some difficulty to access a particular document we use mechanisms of the Law of Access to Information. The results presented also have interviews with coordinators / vice coordinators of the courses that modified their pedagogical projects until 2017. The results of this research are divided into two parts. In the first one, the analyzes of the federal universities of Acre, Amapá, Rondônia, Roraima and Tocantins are presented, which modified their curricula until 2017. Next we present an analysis about the federal universities of Amazonas and Pará, that until the closing of the data collection had changed their projects, but to fulfill the general objective of this research to demonstrate how the pedagogical projects are organized, we carry out this complementary analysis. The hypotheses of this research were partially refuted and we conclude that the objective of adding new knowledge to the Communication research that is done in the North Region was reached. The results of universities that have modified their curricula have pointed out that there is a greater redirection to journalism and its theories and practices in new pedagogical projects. However, there is no shortage of places for the supervised internships and in the training course there is an important percentage of the workload devoted to the practice and daily routine of journalism.